The Early Result of Whole Pelvic Radiotherapy and Stereotactic Body Radiotherapy Boost for High-Risk Localized Prostate Cancer - Lin, Yu-Wei; Lin, Li-Ching; Lin, Kuei-Li (Frontiers in Oncology, 2014)
Purpose The rationale for hypofractionated radiotherapy in the treatment of prostate cancer is based on the modern understanding of radiobiology and advances in stereotactic body radiotherapy (SBRT) techniques. Whole-pelvis irradiation combined with SBRT boost for high-risk prostate cancer might escalate biologically effective dose without increasing toxicity. Here, we report our 4-year results of SBRT boost for high-risk localized prostate cancer. Methods and Materials From October 2009 to August 2012, 41 patients of newly diagnosed, high-risk or very high-risk (NCCN definition) localized prostate cancer patients were treated with whole-pelvis irradiation and SBRT boost. The whole pelvis dose was 45Gy (25 fractions of 1.8Gy). The SBRT boost dose was 21 Gy (three fractions of 7 Gy). Ninety percent of these patients received hormone therapy. The toxicities of gastrointestinal (GI) and genitourinary (GU) tracts were scored by Common Toxicity Criteria Adverse Effect (CTCAE v3.0). Biochemical failure was defined by Phoenix definition. Results Median follow-up was 42 months. Mean PSA before treatment was 44.18 ng/ml. Mean PSA level at 3, 6, 12, 18, and 24 months was 0.94, 0.44, 0.13, 0.12, and 0.05 ng/ml, respectively. The estimated 4-year biochemical failure-free survival was 91.9%. Three biochemical failures were observed. GI and GU tract toxicities were minimal. No grade 3 acute GU or GI toxicity was noted. During radiation therapy, 27% of the patient had grade 2 acute GU toxicity and 12% had grade 2 acute GI toxicity. At 3 months, most toxicity scores had returned to baseline. At the last follow up, there was no grade 3 late GU or GI toxicity. Conclusions Whole-pelvis irradiation combined with SBRT boost for high-risk localized prostate cancer is feasible with minimal toxicity and encouraging biochemical failure-free survival. Continued accrual and follow-up would be necessary to confirm the biochemical control rate and the toxicity profiles.